Deep operator network approximation rates for Lipschitz operators - Schwab, Christoph; Stein, Andreas; Zech, Jakob (Analysis and applications, 2025)
Covers applied analysis techniques & results: approx. theory, asymptot. anal., calculus of var., integral eqs & transforms, ODE, PDE, delay differential eqs, perturbation methods.